Mitigation of Voltage Fluctuations/Voltage Flicker and Power Quality Improvement in Power Systems using Distributed STATCOM - Abubakar Sufyanu (Journal of Power Electronics and Devices, 2020)
This paper primarily deals with power quality and more specifically, voltage flicker in electrical power systems. Voltage flicker is one of the major disturbances in power systems. This voltage flicker occurs mostly due to the presence of nonlinear loads in the system. The amount or magnitude of voltage flicker is dependent on the type of electrical load that is producing the disturbance. Voltage flicker also occurs due to voltage sag and/or voltage swell in a system. The voltage sag could generate inrush current and the inrush current goes through the sensitive load in the distribution system. There are many ways of power quality improvements suing power electronics devices such as FACTS (flexible AC transmission system) devices. The Flexible AC transmission system (FACTS) devices are power electronics-based controllers. It has been proven that these devices can improve transient stability and also help in damping electromechanical oscillations in the distribution power systems. The proposed FACTS device used in this paper is DSTATCOM or Distribution Static Compensator. The D STATCOM will be configured and then designed to reduce the voltage flicker in the system.